7T+8(7T+2)=

Simple and best practice solution for 7T+8(7T+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7T+8(7T+2)= equation:


Simplifying
7T + 8(7T + 2) = 0

Reorder the terms:
7T + 8(2 + 7T) = 0
7T + (2 * 8 + 7T * 8) = 0
7T + (16 + 56T) = 0

Reorder the terms:
16 + 7T + 56T = 0

Combine like terms: 7T + 56T = 63T
16 + 63T = 0

Solving
16 + 63T = 0

Solving for variable 'T'.

Move all terms containing T to the left, all other terms to the right.

Add '-16' to each side of the equation.
16 + -16 + 63T = 0 + -16

Combine like terms: 16 + -16 = 0
0 + 63T = 0 + -16
63T = 0 + -16

Combine like terms: 0 + -16 = -16
63T = -16

Divide each side by '63'.
T = -0.253968254

Simplifying
T = -0.253968254

See similar equations:

| 4(k+5)=2(9k-2) | | 24xy+6y=0 | | 9n-4n=4n+2n+7 | | 2(8n+6)=-3+n | | 5a-2b=8 | | 3c+2(4)=2 | | 21(7-y)+4=-4 | | 2(x-3)+2X=-14 | | 7-3(5-3v)-8=67 | | 6c=c | | x-6-26=7(x-26) | | Y+7-2=-5 | | x-6+26=7(x+26) | | 8(3B+5)+2= | | X^4-10*X^2-3*X+25=0 | | 5n-2n=9 | | 14d-43=-13-7d | | 70+4y=130 | | -4x+20=-4-x | | 2(5a+6)=2(3a+8) | | -2(4b+3)=-8b-7 | | 7(8+9C)= | | 50+4y=130 | | 2(4-1.3x)-4.1x=0.5 | | 6-9x+10c^2= | | -266=-7(8m-2) | | 4x+5=-x+8+5x-3 | | 3f+g=-14 | | x-6+7=26(x+7) | | 7*8-6+3=47 | | S+k+m=180 | | -2x(x+4)+6=-3 |

Equations solver categories